Analysis Of Operational Cost Budget As A Management Control Tool At Pt. Pln (Persero) Nusantara Power UPDK Bakaru Kota Parepare - Siti Nurfazila (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
This study aims to determine the process of preparing the operational cost budget at PT. PLN (Persero) Nusantara Power UPDK Bakaru Kota Parepare, to find out the management control system at PT. PLN (Persero) Nusantara Power UPDK Bakaru Kota Parepare, as well as knowing the operational cost budget as a management control tool. Data collection was carried out by way of field research to obtain data sourced from PT. PLN (Persero) Nusantara Power UPDK Bakaru Kota Parepare, through observation, interviews, and documentation. Data analysis in this study was carried out by direct research on respondents at PT. PLN (Persero) Nusantara Power UPDK Bakaru City of Parepare. After going through the analysis process, the result is the process of preparing the PT. PLN (Persero) Nusantara Power UPDK Bakaru Kota Parepare uses a bottom-up approach. The management control system used by PT. PLN (Persero) Nusantara Power UPDK Bakaru Kota Parepare so far has been appropriate. Starting from planning, coordination, communication, evaluation, and decision-making. The operational cost budget functions as a management control tool, where the one-year operational cost budget is used to plan the amount of the following year's operational costs and is based on the previous year's budget.